Influence of stakeholder interactions on policy: The broad-based socio-economic empowerment charter for the South African Mining and Minerals Industry - Day, Christopher John (Stellenbosch : Stellenbosch University, 2021)
Thesis (MA)--Stellenbosch University, 2021.